Guimarães, from its origins to UNESCO: urban history and heritage challenges - Correia, Jorge (2019)
The subject of this lecture spins around Guimarães, a medium-sized city in Northern Portugal, home to my school of architecture and research centre, with a Unesco world-heritage historical centre. Revisiting its urban history and discovering its process of requalification provide important bridges to face Koya’s current heritage challenges. Guimarães was founded by a countess in the 10th century. A convent in the lower area and a castle in the upper area enabled a bipolarization of the city, with the consolidation of those two nuclei: pilgrimage and protection. The long medieval period saw the building of a wall and the unification of both poles as well as the settlement of new Gothic monasteries. Early Modern time further expanded Guimarães to the outskirts, counting with the presence of important master builders in the city. From 18th to 20th centuries, the city counted with a strong industrialization that provided a sense of modernity and a significant urban growth. For all these reasons, and considering it was the birthplace of the first Portuguese king and the starting point to the formation of the kingdom, Guimarães possesses a strong identity and still plays an important role in the country. Part of this role model derives from the conservation of its historical core. In fact, soon after democracy was established in Portugal in 1974, the municipality elaborated a plan of urbanization, calling one of the most distinguished architects of the second half of the 20th century - Fernando Távora. In his words, it would be ‘a plan of synthesis, compromising unity and diversity, general and particular, function and design, past and future’. Further on, in 1983, the Historical Centre Office, later called Local Technical Office, was created and installed in a renewed house of the old centre, to assist interventions with proximity. Work was devoted to public space design and scientific or technical counselling to private owners, all in order to respect the visual atmosphere of the quarters. Plus, protocols at local, regional and national levels were established to address monuments and landmarks. As a consequence, applying for world heritage status came as a natural sequence over a two-decade process and Guimarães was awarded the title in 2001, boosting tourism figures. This impetus did not stop then and new applications provided fertile opportunities for the continuation of urban requalification, such as the European Capital of Culture in 2012, embracing design for the 21st century as a contemporary reflexion within the city’s strong identity and longue durée. The process pursues these days, with new initiatives of surveying heritage or enhancing old building with new functions, in collaboration with the university, or extending the heritage awareness beyond the historical heart towards the rest of the municipality territory. Overall, strategies, models, and procedures applied in Guimarães make it as a successful example, a learning case study for decaying urban assemblages such as the old town of Koya.